Feasible threats by manipulating tunneling packet on 6to4 network - Utomo Yusuf, Rizki Munawir; Bahaman, Nazrulazhar; Hassan, Aslinda (2014)
Tunneling mechanism becomes the most delicate transition mechanism compared to other transition mechanism, Dual Stack and Address Translation because tunneling offers easier way to start migrating from IPv4 to IPv6 and offers a smooth transition. 6to4 tunneling is automatic tunneling to conquer migration issues. In fact, tunnel transition mechanism is believed to be susceptible from several type of attacks. On 6to4 tunneling, Neighbor Discovery Protocol message becomes a potential media to exploit by attacker. It starts with deploying a controlled testbed network environment and running several scenario DoS attack by manipulating NDP message through 6to4 tunneling. The expected result is to prove that attacking methods is feasible and effective.